PENINGKATAN KINERJA PEGAWAI MELALUI PROGRAM PELATIHAN DAN ETOS KERJA DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI LEMBAGA PERKREDITAN DESA SE-KECAMATAN BULELENG - Kartika Ningsih, Luh; Dian Wahyuni, Kadek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
In this study, it is intended to analyze skills development related to the role of training programs and the ethos mediated by work discipline. The author conducted a study at Village Credit Institutions in Buleleng District. The population in the study was 100 people by taking a sample of 80 LPD employees, randomly (proportional random sampling) and using the slovin formula. The measurement tool used is SEM-PLS. the analysis examines the outer model and the structural model (inner model). then testing the hypothesis along with the mediating effect. The results showed that there were 7 relationships studied, namely the effect of training programs on work discipline (0.764 < 1.96), work ethic with values ??(7.996 > 1.96) meaning, there was an influence with work discipline, there was an influence of training programs on employee performance ( 11.854 > 1.96), work ethic influences employee performance (2.158 > 1.96), there is a significant relationship between work discipline and employee performance (2.357 > 1.96), work discipline is unable to mediate training programs and employee performance (0.733 > 1.96), work discipline variables can fully mediate between work ethic and employee performance (2.131> 1.96).